Identification of wheat leaf rust (Puccinia triticina. ERIKS.) genes expressed during the early stages of infection - Segovia, Vanesa (Kansas State University, 2010)
In Kansas, wheat (Triticum aestivum L.) is severely affected by the biotrophic fungus Puccinia triticina (leaf rust). Although resistant varieties have been developed, the fungus tends to overcome new sources resistance very quickly. Plants have evolved a single gene (R genes) defense network that can recognize specific pathogen effectors (Avr), in a gene-for-gene manor. In rusts, effectors are secreted proteins responsible for inducing the uptake of nutrients and inhibit host defense responses. Identification of secreted proteins during the infection may help to understand the mode of infection of P. triticina. Little is known about molecular interactions in the pathosystem wheat-leaf rust and no Avr genes from cereal rusts have been cloned. In order to understand pathogenicity in leaf rust and generate new alternatives for disease control, the goal of this research is identify P. triticina secreted proteins from a collection of expressed genes during the infection, and to characterize putative Avr function for three candidates. From 432 EST’s derived from haustoria and infected plants, fifteen secreted proteins were identified and 10 were selected as potential avirulence candidates. Pt3 and Pt 51 are two P. triticina (Pt) candidates expressed specifically in the haustoria and encode small cysteine-rich secreted proteins. Eight candidates are expressed at early stages of infection, during spore germination and 6 days after inoculation. They are small-secreted proteins. None are repetitive elements or have nuclear localization signals. They also do not share a conserved motif with known filamentous fungus Avr proteins. Five candidates are novel proteins, two have similarity with predicted proteins, one is homologous with Hesp-379-like protein, one is homologous with superoxide dismutase, and one has a cell glucanase predicted function. Pt3, Pt12 and Pt27 were tested by transient expression experiments using co-bombardment with GUS into leaf rust resistant isogenic lines. Reduction in the expression of reporter gene GUS co-expressed with Pt27 indicates a potential avirulence factor for Lr26 in wheat.
Keywords: Puccinia triticina; Triticum aestivum; EST; Secreted proteins; Agriculture, Plant Pathology (0480)